Penguatan Pengelolaan Tenaga Lepas melalui Digitalisasi di UPA Pertanian Terpadu - Ratih Puspitorini Yekti Ambarkahi; Dyah Kusuma Wardani; Fredy Eka Ardhi Pratama; Ponti Primastuti Aulia Nugraheni; Pascawati Savitri Universitasari; Dhanang Eka Putra (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The 2025 Community Service Program was carried out at the Integrated Agriculture Academic Support Unit (UPA Pertanian Terpadu) of Politeknik Negeri Jember, which oversees four Teaching Factory (TEFA) units: TEFA Smart Green House, TEFA Livestock, TEFA Innovation Garden, and TEFA Chrysanthemum. The partner's main problem was the manual management of 25 temporary workers, which led to inefficiencies, delays in task distribution, and weak performance monitoring. The program was implemented through needs assessment and analysis; design of a simple application-based digital system; user training; intensive mentoring; and the provision of fingerprint attendance machines. The results show that the digital system and fingerprint attendance machines improved the efficiency of task distribution, accelerated recording and reporting processes, and made it easier to monitor worker performance. Digital literacy among temporary workers increased by an average of 40% based on pre–post tests, and delays in monthly production reports decreased noticeably. Worker satisfaction also increased due to clearer task allocation, transparent working hours, and more accurate incentive recording.